Histone Lysine Methyltransferase SETD2 Regulates Coronary Vascular Development in Embryonic Mouse Hearts - Chen, Fengling; Chen, Jiewen; Wang, Hong; Tang, Huayuan; Huang, Lei; Wang, Shijia; Wang, Xinru; Fang, Xi; Liu, Jie; Li, Li; Ouyang, Kunfu; Han, Zhen (Frontiers in Cell and Developmental Biology, 2021)
Congenital heart defects are the most common birth defect and have a clear genetic component, yet genomic structural variations or gene mutations account for only a third of the cases. Epigenomic dynamics during human heart organogenesis thus may play a critical role in regulating heart development. However, it is unclear how histone mark H3K36me3 acts on heart development. Here we report that histone-lysine N-methyltransferase SETD2, an H3K36me3 methyltransferase, is a crucial regulator of the mouse heart epigenome. Setd2 is highly expressed in embryonic stages and accounts for a predominate role of H3K36me3 in the heart. Loss of Setd2 in cardiac progenitors results in obvious coronary vascular defects and ventricular noncompaction, leading to fetus lethality in mid-gestation, without affecting peripheral blood vessels, yolk sac and placenta formation. Furthermore, deletion of Setd2 dramatically decreased H3K36me3 level and impacted the transcriptional landscape of key cardiac related genes, including Rspo3 and Flrt2, which are downstream targets of H3K36me3. Taken together, our results strongly suggest that SETD2 plays a primary role in H3K36me3, and is critical for coronary vascular formation and heart development in mice.